Relationship Marketing, Switching Costs dan Service Quality terhadap Customer Satisfaction dan pada akhirnya Membentuk Customer Loyalty pada PT. Lautan Indomasutama Medan - Vanessa Vanessa; Oliandes Sondakh; Amelia Amelia (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine and analyze relationship marketing, switching costs and service quality on customer satisfaction and ultimately forming customer loyalty. The population in this study was 141 customers. The number of samples in this research was 68 customers who used freight forwarding services. The data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The research results show that relationship marketing has a significant effect on switching costs, service quality has a significant effect on switching costs, relationship marketing has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, relationship marketing has a significant effect on customer loyalty, service quality has a significant effect on customers loyalty, switching costs have a significant effect on customer loyalty and customer satisfaction has a significant effect on customer loyalty. The conclusion is that the important role of relationship marketing and maximized service quality can encourage switching costs, customer satisfaction and customer loyalty. Keywords: Customer Satisfaction, Customer Loyalty, Relationship Marketing